Developing an Effective Team Work: The Effect of Collaborative Learning Strategies on Improving Team Work Abilities in Buddhist Sunday School - Depi Setiyawati; Widiyanto Widiyanto; Susanto Susanto; Widi Astuti; Komang Sutawan; Eko Pramono; Dedi Kundana; Tejo Ismoyo (International Journal of Science and Applied Science: Conference Series, 2024)
The research puropse is to deepen the effect of collaborative learning strategies on improving students' cooperation skills in Buddhist Sunday schools. One of the problems faced in the learning process in Buddhist Sunday schools is that some students do not show good cooperation. In addition, some students are less interested in participating in these activities, which is caused by a dislike of the learning methods applied. This study uses a quantitative approach with a survey method. The study population consisted of 44 students, with a sample of 15 students taken through a sampling technique from another monastery. The study was conducted at a Buddhist Sunday school in a monastery, with respondents from students in the 2024/2025 academic year. The analysis results using simple linear regression indicate that collaborative learning strategies significantly affect cooperation among Buddhist Sunday school students. The research has limitation in the period of time to deepen the study and for the next researcher to develop the methodology on do the deeply observation with a case study method.